A Comparison of Multimedia and Traditional Paper Assignments in an Introductory Psychology Course. (April 2022) - Riordan, Monica A.; Abo-Zebiba, Zamen; Marsh, Joseph
Background: Multimedia creation and curation for assignments have the potential to engage students in deeper learning. Objective: This study explored whether the same homework assignments delivered in paper versus multimedia format resulted in different student experiences. Method: Introductory psychology students submitted either traditional papers or multimedia projects to address the same assignment prompt, a process that was repeated seven times throughout four courses and was either instructor-determined or student-selected. Students were surveyed about the assignment formats, and assignment grades were analyzed. Results: Overall, students found the multimedia assignments more engaging, more enjoyable, more interesting, and more difficult than paper assignments. When assignments were instructor-determined, students reported higher perceived learning for the multimedia assignments. Assignment grades were not significantly different between assignment formats. Conclusion and teaching implications: These results suggest that moving traditional paper assignments into a multimedia format is a no-cost way to improve the student experience.